Bank-specific shocks and house price growth in the U.S. - Franziska Bremus; Thomas Krause; Felix Noth (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
This paper investigates the link between mortgage supply shocks at the banklevel and regional house price growth in the U.S. using micro-level data on mortgage markets from the Home Mortgage Disclosure Act for the 1990-2014 period. Our results suggest that bank-specific mortgage supply shocks indeed affect house price growth at the regional level. The larger the idiosyncratic shocks to newly issued mortgages, the stronger is house price growth. We show that the positive link between idiosyncratic mortgage shocks and regional house price growth is very robust and economically meaningful, however not very persistent since it fades out after two years.
urn:nbn:de:gbv:3:2-67714
Keywords: E44; G21; R20; 330; house prices; idiosyncratic shocks; granularity; credit supply